2013
DOI: 10.7124/bc.00082a
|View full text |Cite
|
Sign up to set email alerts
|

The areas of application for plant lectins

Abstract: Lectins, in particular from plants, are proteins of non-immune origin that are able to bind carbohydrates with high specificity. Due to their properties, phytolectins are of great interest in practical applications. They were shown to play an important role in forming strategies for treatment of disease including cancer and HIV. Plant lectins are an important tool in glycomic studies. Plant lectins with fungicidal and insecticidal activities are used in transgenic technologies to increase plant resistance to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
0
6
0
3
Order By: Relevance
“…; Melnykova et al . ). In this study, we identified that ConA is effective in inhibiting the initial attachment and biofilm development of E. coli and L. monocytogenes .…”
Section: Discussionmentioning
confidence: 97%
“…; Melnykova et al . ). In this study, we identified that ConA is effective in inhibiting the initial attachment and biofilm development of E. coli and L. monocytogenes .…”
Section: Discussionmentioning
confidence: 97%
“…Óïðîäîâae ìèíóëèõ äåñÿòèë³òü âàãîìå ì³ñöå â àðñåíàë³ ³íñòðóìåíò³â äîñë³äaeåííÿ ´ë³êîêîäó aeèâèõ îð´àí³çì³â çàâîþâàëè ìåòîäè ëåê-òèíîâî¿ ã³ñòîõ³ì³¿ [8][9][10][11][12][13][14][15][16][17][18][19][20]. Âîëîä³þ÷è óí³êàëüíîþ âëàñòèâ³ñòþ âèá³ðêîâî çâ'ÿçóâàòèñÿ ç òåðì³íàëüíèìè ìîíî-÷è äèñàõàðèäíèìè çàëèøêàìè îë³ãîñàõàðèäíèõ ëàíöþã³â ´ë³êîïîë³ìåð³â, ëåêòèíè äîçâîëÿþòü îòðèìàòè äîñòîâ³ðíó ³íôîðìàö³þ ùîäî ¿õíüî¿ ã³ñòîòîïî´ðàô³¿, ïåðåáóäîâè ïðè ðåà-ë³çàö³¿ ïðîöåñ³â åìáð³î´åíåçó, ó äèíàì³ö³ ô³ç³î-ëî´³÷íèõ â³äïðàâëåíü òà ðîçâèòêó ð³çíîìàí³òíèõ ôîðì ïàòîëî´³¿.…”
Section: îãëÿäè ë³òåðàòóðèunclassified
“…Âîëîä³þ÷è óí³êàëüíîþ âëàñòèâ³ñòþ âèá³ðêîâî çâ'ÿçóâàòèñÿ ç òåðì³íàëüíèìè ìîíî-÷è äèñàõàðèäíèìè çàëèøêàìè îë³ãîñàõàðèäíèõ ëàíöþã³â ´ë³êîïîë³ìåð³â, ëåêòèíè äîçâîëÿþòü îòðèìàòè äîñòîâ³ðíó ³íôîðìàö³þ ùîäî ¿õíüî¿ ã³ñòîòîïî´ðàô³¿, ïåðåáóäîâè ïðè ðåà-ë³çàö³¿ ïðîöåñ³â åìáð³î´åíåçó, ó äèíàì³ö³ ô³ç³î-ëî´³÷íèõ â³äïðàâëåíü òà ðîçâèòêó ð³çíîìàí³òíèõ ôîðì ïàòîëî´³¿. Ëåêòèíè äîçâîëÿþòü ñåëåêòèâíî âèÿâëÿòè îêðåì³ ñóáïîïóëÿö³¿ êë³òèí, îð´àíåëè, ïîâ'ÿçàí³ ç ïðîöåñèíãîì ´ë³êîïîë³ìåð³â, à òàêîae ä³ëÿíêè ïëàçìàòè÷íî¿ ìåìáðàíè, çàä³ÿí³ ó òèõ ÷è ³íøèõ ìåõàí³çìàõ êë³òèííî¿ àêòèâíîñò³ [11,16,[21][22][23][24][25][26][27].…”
Section: îãëÿäè ë³òåðàòóðèunclassified
“…The Phaseolus vulgaris beans are rich sources of lectins in human diet, and it has become clear that this kind of proteins can cause diseases, as their biologically and immunologically intact forms are resistant to digestion in the body (Bardocz et al, 1995;Woodley, 1999). Although complete proof is still lacking in most cases, lectins have been considered by most biomedical scientists for use in therapy in a variety of diseases (Freed, 1991;Mascanfroni et al, 2011;Lam and Ng, 2011b;Melnykova et al, 2013). Thus, increasing concerns are currently established about the safety and efficacy of the Phaseolus vulgaris lectins as shown in Table 1.…”
Section: The Potential Health Implications Of Phaseolus Vulgaris Lectinsmentioning
confidence: 99%